Multicriteria Decisions in Urban Energy System Planning: A Review - Cajot, Sébastien; Mirakyan, Atom; Koch, Andreas; Maréchal, François (Frontiers in Energy Research, 2017)
Urban energy system planning (UESP) is a topic of growing concern for cities in deregulated energy markets, who plan to decrease energy demand, reduce their dependency on fossil fuels, and increase the share of renewable energy sources. UESP being a highly multi-sectoral and multi-actor task, multi-criteria decision analysis (MCDA) methods are frequently used in the decision processes. These methods may provide support in organizing and identifying solutions to problems with conflicting objectives. However, knowing which method to use is generally not straightforward, as the appropriateness of a method or combination of methods depends on the decision problem’s context. This article therefore reviewed scientific papers to characterize and analyze MCDA problems and methods in the context of UESP. The review systematically explores issues such as the scope of the problems, the alternatives and criteria considered, the expected decision outcomes, the decision analysis methods and the rationales for selecting and combining them, and the role of values in driving the decision problems. The final outcome is a synthesis of the data and insights obtained, which may help potential users identify appropriate decision analysis methods based on given problem characteristics.